2012
DOI: 10.1038/ncomms2257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of the assembly of an acid-sensing receptor ion channel complex

Abstract: Polycystic kidney disease (PKD) family proteins associate with transient receptor potential (TRP) channel family proteins to form functionally important complexes. PKD proteins differ from known ion channel-forming proteins and are generally thought to act as membrane receptors. Here we find that PKD1L3, a PKD protein, functions as a channel-forming subunit in an acid-sensing heteromeric complex formed by PKD1L3 and TRPP3, a TRP channel protein. Single amino acid mutations in the putative pore region of both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 51 publications
8
75
0
Order By: Relevance
“…It is generally believed that, in the polycystin complexes, TRPP subunits form an ion channel, whereas the PKD subunit receives the extracellular signal as a sensor or receptor (2,6). However, our recent study showed that PKD1L3 is also a channel pore-forming subunit (25), suggesting that other PKD proteins may also function as an ion channel subunit in their complexes with TRPPs.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…It is generally believed that, in the polycystin complexes, TRPP subunits form an ion channel, whereas the PKD subunit receives the extracellular signal as a sensor or receptor (2,6). However, our recent study showed that PKD1L3 is also a channel pore-forming subunit (25), suggesting that other PKD proteins may also function as an ion channel subunit in their complexes with TRPPs.…”
mentioning
confidence: 78%
“…The downstream region of this trimer forms the PKD1-binding site and binds to one copy of the C-terminal coiled-coil domain of PKD1, determining a 3:1 (TRPP2/PKD1) subunit stoichiometry of the full-length complex (29,30). Our recent study concluded that this 3:1 stoichiometry is shared by the TRPP3-PKD1L3 complex (25), suggesting a common assembly mechanism among all polycystin complexes. Although several other domains and amino acids were found to be involved in TRPP2 homomeric assembly (31,32), so far, the C-terminal coiled-coil domain is the only site shown to be directly involved in its assembly with PKD1.…”
mentioning
confidence: 94%
“…TEVC experiments were performed as described previously (49). In brief, cRNAs were synthesized in vitro and injected into follicle membrane free oocytes (50 ng of cRNA per oocyte).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described previously (49). Protein samples were run on 4-12% Bolt Bis-Tris Plus gels (Life Technologies) and transferred to a PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation